Christianity and Christians in Shakī and Shīrvān from the Earliest Times Until the end of the Safavid Era - Kristine Kostikyan; Gevorg Stepanyan; Gohar Mkhitaryan (Banber Arevelagitut'yan Instituti)
The paper examines the religious aspects of the history of Shakī and Shīrvān regions of Eastern Caucasus from the times of the spread of Christianity there until the end of Safavid rule over it. An overview of the history of the Church of Albania (or Ağuank‘), its legal and political aspects conducted in the article are important for a better understanding of its relations with the Armenian Apostolic Church, and identity issues of its subject Christian population. An empirical and comparative-historical analysis of the data and information con-tained in historical sources on the situation of Christians in the regions of Shakī and Shīrvān provides a clear view of the realities and situation in each phase of history and the factors stimulating their conversion to Islam. The study shows that during Safavid predominance over the regions included in one administrative unit of Shīrvān bīglarbīgī the cultural and civil methods of assimilation and conversion, combined with economic incentives, prevailed. The gradual weakening of Safavid rule over the regions was accompanied with serious challenges and hardships faced by local Christians during the frequent invasions of North Caucasian tribes. The collapse of Safavid rule in the regions designated the end of religious tolerance and intensification of the use of forced and economic methods of conversion to Islam.